2010
DOI: 10.1007/s12098-010-0188-9
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Pneumococcal Diseases and Serotypes: Can Vaccines Protect?

Abstract: Pneumococcal disease may develop despite prior vaccination. The expanded coverage of newer polyvalent pneumococcal vaccines might have prevented some, but not all, of these admissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 15 publications
2
15
0
1
Order By: Relevance
“…We previously reported that bacterial coinfections were found in nearly 20% of PICU admissions associated with respiratory virus infections [3]. S pneumoniae was notoriously associated [3,18]. Our findings were in agreement with those reported by ourselves as well as other investigators [3,[18][19][20].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We previously reported that bacterial coinfections were found in nearly 20% of PICU admissions associated with respiratory virus infections [3]. S pneumoniae was notoriously associated [3,18]. Our findings were in agreement with those reported by ourselves as well as other investigators [3,[18][19][20].…”
Section: Discussionsupporting
confidence: 93%
“…S pneumoniae was notoriously associated [3,18]. Our findings were in agreement with those reported by ourselves as well as other investigators [3,[18][19][20]. Comparing the 3 common viruses in PICU admissions, the mean age of children admitted with RSV was lower than of those with influenza or parainfluenza (1.2 vs 5.6 vs 2.4 years, P = .003) [3].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Pneumococcus is an important pathogen in childhood [1][2][3]. Invasive pneumococcal disease refers to unlocalised bacteremia, pneumonia, or meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive pneumococcal disease refers to unlocalised bacteremia, pneumonia, or meningitis. Despite the availability of effective vaccines, new serotypes continue to evolve [1][2][3]. The Hong Kong Government introduced the 7-valent polysaccharide vaccine in September 2009.…”
Section: Discussionmentioning
confidence: 99%